Custeio e tarifaç\~ao dos serviços públicos urbanos essenciais: Análise comparativa - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This discussion paper presents a comparative analysis of the market structure and charging of the main public services charged, considering some tariff charging parameters raised for each of them. The services considered in the analysis are sanitation, waste, transport, energy and telephony tariffs, with the main parameters analyzed referring to the scope of payment by per capita income range, payment's covery by families, analysis of payment progressivity, in addition to aspects such as payment for availability, tariff diversification, social discounts and cross-subsidization. The objective of the comparative analysis is to try to identify the main similarities and differences in public tariff charging policies for selected public services in order to identify distortions or opportunities for improvement in the collection structure of these segments.
Keywords: H20; 330; pricing; costing; essential urban services; urban transport; energy; solid waste; telephony; sanitation; tariff policy services